Analisis Noise Pada Radiografi Thorax Pulmonum Pada Penerapan Modifikasi Faktor Eksposi Aturan 10 kV - Luthfi Rusyadi; Siti Daryati; Dwi Rochmayanti; Andrey Nino Kurniawan (Poltekkes Kemenkes Semarang, 2021)
Introduction: Quality and dose factors are very important in radiodiagnostics. To produce a constant radiographic quality, the density and contrast produced must remain constant. There is a rule that aims to produce a constant radiographic quality by adding the exposure value, namely the 10 kV rule. This study was conducted to determine the noise in the computed radiography image with the thorax organ produced by modifying the exposure factor of the 10 kV rule and whether it is still within tolerance.Methods: This quantitative research was conducted with an experimental approach. This is done by taking a series of radiographs that include three exposure factor settings, standard (60 kV, 10 mAs), increased by 10 kV (70 kV, 5 mAs) and lowered by 10 kV (50 kV, 20 mAs). Noise measurement is done by doing ROI in the background area. The exposure index and deviation index values were also recorded as quality and dose references. The data was processed and analyzed by statistical tests.Results: From the statistical test results, there is a significant relationship between kV and noise with a sig (1-tailed) of ,000. Noise on the standard exposure factor has a lower noise than the modified exposure factor with a difference of 0.2. From the quality aspect, the most optimum exposure index and deviation index indicators are in the range of 70 KV and 5 mAs.Conclusion: The results of the statistical test of the relationship of kV to noise obtained at 50 Kv and 20 mAs, 60 kV and 10 mAs gave a significance value of 0.263 and 0.435, while at 70 kV and 10 mAs with Sig. (1-tailed) of .000 which means the relationship between kV to noise is strong because the sig value is below 0.05.